Determinants of household food access among small farmers in the Andes: Examining the path - Leah, J.; Pradel, W.; Cole, Donald C.; Prain, Gordon; Creed-Kanashiro, Hilary M.; Carrasco, M.V. (Cambridge University Press, 2013)
Household food access remains a concern among primarily agricultural households in lower- and middle-income countries. We examined the associations among domains representing livelihood assets (human capital, social capital, natural capital, physical capital and financial capital) and household food access.Cross-sectional survey (two questionnaires) on livelihood assets.Metropolitan Pillaro, Ecuador; Cochabamba, Bolivia; and Huancayo, Peru.Households (n570) involved in small-scale agricultural production in 2008.Food access, defined as the number of months of adequate food provisioning in the previous year, was relatively good; 41 % of the respondents indicated to have had no difficulty in obtaining food for their household in the past year. Using bivariate analysis, key livelihood assets indicators associated with better household food access were identified as: age of household survey respondent (P= 0·05), participation in agricultural associations (P= 0·09), church membership (P= 0·08), area of irrigated land (P= 0·08), housing material (P= 0·06), space within the household residence (P= 0·02) and satisfaction with health status (P= 0·02). In path models both direct and indirect effects were observed, underscoring the complexity of the relationships between livelihood assets and household food access. Paths significantly associated with better household food access included: better housing conditions (P= 0·01), more space within the household residence (P= 0·001) and greater satisfaction with health status (P= 0·001).Multiple factors were associated with household food access in these peri-urban agricultural households. Food security intervention programmes focusing on food access need to deal with both agricultural factors and determinants of health to bolster household food security in challenging lower- and middle-income country contexts.